On how QCD gauge invariance gets realized in the context of effective locality - Fried, H. M.; Grandou, Thierry; Hofmann, Ralf (Advances in high energy physics, 2018)
The fermionic Green’s functions of QCD exhibit an unexpected property of effective locality, which appears to be exact, involving no approximation. This property is nonperturbative, resulting from a full integration of the elementary gluonic degrees of freedom of QCD. Recalling, correcting, and extending the derivations of effective locality, focus is put on the way nonabelian gauge invariance gets realized in the fermionic nonperturbative regime of QCD.